IMPLEMENTASI MANAJEMEN PENGETAHUAN PADA PERPUSTAKAAN STAIN PADANGSIDIMPUAN - Yusri Fahmi (Pustakaloka, 2013)
Library for a higher education is a center even a heart of thisinstitution, but with the internet, users prefer this new technology than libraries. To solve this problem it must strive to provide information for the most appropriate time, using most appropriate resources, and budget. Library of the State College for Islamic Studies Padangsidimpuan is challenged to give excellent service for the users with minimal budget, so the performance is impaired.This article explores the use of knowledge management to solve the above problem. The implementation of the knowledge management is done by carrying out human resources, knowledge sharing, and information and technology empowering